Analysis of energy efficiency improvement of high-tech fabrication plants. (12th August 2019) - Hu, Shih-Cheng; Lin, Tee; Fu, Ben-Ran; Chang, Cheng-Kung; Cheng, I-Yun
Abstract: In this study, we developed simulation software for the energy consumption of high-tech fabrication plants. The developed fab energy simulation (FES) featured more detailed characteristics of the subsystems than existing simulation tools. The calculated results of the FES were validated using the annual operating data of a Taiwanese semiconductor manufacturing fab. The measured data indicated three major energy consumers in the studied fab—the process tool, water chiller and clean dry air systems. The annual consumption of electricity calculated with the FES showed a deviation of only −0.73% compared with the measured data. The calculated results exhibited an energy consumption trend that was very similar to the measured data, indicating the reliability of the FES. The FES results also demonstrated excellent agreement with the calculated results of the commercial tool 'CleanCalc II'. Additionally, the FES was employed to study the energy consumption under different conditions. The results revealed that the energy consumption of the chiller system reduced significantly by 43.7% when the chiller system with a coefficient of performance of 8 was used. This reduction in the energy consumption corresponded to 10% of the total energy consumption in the fab, indicating significant energy-saving potential.